(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
From a well-preserved fossil assemblage of the mid-Pliocene (Piacenzian) Monte Padova section near Castell’Arquato (northern Italy), three cheilostome bryozoan species are described and figured. The dome-shaped, free-living Cupuladria bugei Reguant, described from the Pliocene of the eastern Atlantic, is characterised using SEM photography for the first time, and the present finding is the first from the Mediterranean realm. Similarly, the encrusting unilaminar Cleidochasmidra canakkalense Ünsal & d’Hondt, occasionally occurring independently of a substrate, was described from the Recent Mediterranean Sea but hitherto lacked a thorough SEM-based description. It has previously been reported only once from the Pliocene of Italy. Plesiocleidochasma mediterraneum Chimenz Gusso & Soule, occurring as uni- to plurilaminar encrustations or free of a substrate, was only recently described from the Mediterranean Sea while our finding represents its first fossil occurrence. For the latter two species no information on ancestrula morphology and early colony development was, until now, available from the existing literature.